ANALISIS TREN PENELITIAN PANGAN FUNGSIONAL: KATEGORI BAHAN SERAT PANGAN [Functional Food Research Trend Analysis: Dietary Fiber Category] - Diah Anggraeni Jatraningrum (Jurnal Teknologi dan Industri Pangan, 2012)
Functional food, such as probiotic, prebiotic, dietary fiber, vitamin, flavonoid etc, is one of the convergent products between foods and pharmaceutical industry. Dietary fiber, as a part of functional food, is showing a rapid increment in publications and patents. This review will try to give more information about the current advancement in dietary fiber research in Indonesia versus global research trend and also to compare patentability of research in dietary fiber. There are five technology in dietary fiber that will be highlighted; formulation-process-fortification, extraction-isolation-purification, fermentation, metabolic and biotechnology. Research evaluation between dietary fiber research data in the Indonesian Institute of Science (LIPI) and global publications and patents show that dietary fiber have chance to be developed become new product with a convergent category in functional food. Dietary fiber with probiotic or prebiotic for is as an example.